Efficacy of Lactoferrin with Standard Triple Therapy or Sequential Therapy for Helicobacter pylori Eradication: A Randomized Controlled Trial - Hablass, Fahmy H.; Lashen, Sameh A.; Alsayed, Eman A. (Turkish Journal of Gastroenterology, 2021)
Background: Bovine lactoferrin addition to regimens of Helicobacter pylori treatment has been tried, with conflicting results. Aim: To assess the effect of bovine lactoferrin in addition to the anti-H. pylori treatment. Methods: We enrolled 400 H. pylori-infected patients who were randomized into 4 equal groups: (A): proton-pump-based triple therapy (PpTT) for 2 weeks, (B): sequential therapy for 2 weeks, (C): proton-pump-based triple therapy plus bovine lactoferrin for 2 weeks, and (D): sequential therapy plus bovine lactoferrin for 2 weeks. Results: In the per-protocol analysis, the success in groups A, B, C, and D were 70.3%, 82.8%, 85.6%, and 94.5%, respectively (P < .001). The treatment success rate for the sequential therapy plus bovine lactoferrin regimen was significantly higher than that with sequential therapy alone (94.5% vs. 82.8%, P = .013). The same applied for proton-pump-based triple therapy (85.6% vs. 70.3%, P = .014). The addition of bovine lactoferrin and the presence of endoscopic corpus gastritis were independent predictors for successful eradication of H. pylori. Conclusion: Bovine lactoferrin could hasten the effectiveness of the proton-pump-based triple therapy or sequential therapy for H. pylori eradication.